A Clinical Perspective on the Dietary Therapies for Pediatric Eosinophilic Esophagitis: The Gap Between Research and Daily Practice - De Vlieger, Liselot; Smolders, Lieselot; Nuyttens, Lisa; Verelst, Sophie; Breynaert, Christine; Vanuytsel, Tim; Hoffman, Ilse; Bullens, Dominique MA (Frontiers in Immunology, 2021)
Pediatric eosinophilic esophagitis (ped-EoE) is an immune-mediated pathology affecting 34 per 100.000 children. It is characterized by an esophageal inflammation caused by an immune response towards food antigens that come into contact with the esophageal lining. Depending on the age of the child, symptoms can vary from abdominal pain, vomiting and failure to thrive to dysphagia and food impaction. The diagnosis of this chronic disease is based on the symptoms of esophageal dysfunction combined with an infiltration of more than 15 eosinophils per high-power field and the exclusion of secondary causes. The treatment modalities include the 3Ds: Drugs, allergen avoidance by Diet and/or esophageal Dilation. In this review we focused on the efficacy of dietary approaches in ped-EoE, which currently include the elemental diet, the empiric elimination diet and the allergy test-directed elimination diet. Although several reviews have summarized these dietary approaches, a lack of consistency between and within the elimination diets hampers its clinical use and differences in subsequent reintroduction phases present a barrier for dietary advice in daily clinical practice. We therefore conducted an analysis driven from a clinician’s perspective on these dietary therapies in the management of ped-EoE, whereby we examined whether these variations within dietary approaches, yet considered to be similar, could result in significant differences in dietary counseling.